2015
DOI: 10.1124/mol.115.098822
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Cholestasis Leads to Repressed CYP2D6 Expression in CYP2D6-Humanized Mice

Abstract: Cholestasis activates bile acid receptor farnesoid X receptor (FXR) and subsequently enhances hepatic expression of small heterodimer partner (SHP). We previously demonstrated that SHP represses the transactivation of cytochrome P450 2D6 (CYP2D6) promoter by hepatocyte nuclear factor (HNF) 4a. In this study, we investigated the effects of estrogeninduced cholestasis on CYP2D6 expression. Estrogen-induced cholestasis occurs in subjects receiving estrogen for contraception or hormone replacement, or in susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Together with the literature results, our findings suggest that the effects of retinoids on CYPs are complex and involve multiple nuclear receptors. 8,32,33 It is possible that endogenous regulators of these pathways in vivo, such as bile acids, and stellate cell and Kupffer cell-derived factors, are not well represented in vitro resulting in IVIVE disconnect. Induction of Cyp2d in mice and CYP2D6 in the clinical study is in agreement with the observed increase in Cyp2d11, Cyp2d22, Cyp2d26, and Cyp2d40 mRNA and activity in mice during pregnancy and corresponding increase in RA signaling in the maternal liver during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the literature results, our findings suggest that the effects of retinoids on CYPs are complex and involve multiple nuclear receptors. 8,32,33 It is possible that endogenous regulators of these pathways in vivo, such as bile acids, and stellate cell and Kupffer cell-derived factors, are not well represented in vitro resulting in IVIVE disconnect. Induction of Cyp2d in mice and CYP2D6 in the clinical study is in agreement with the observed increase in Cyp2d11, Cyp2d22, Cyp2d26, and Cyp2d40 mRNA and activity in mice during pregnancy and corresponding increase in RA signaling in the maternal liver during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Female subjects using oral contraceptives can be considered a potential interfering factor for this analysis due to the fact that hormones such as progesterone, testosterone, pregnanolone, pregnenolone, 17β-estradiol, and 17β-hydroxyprogesterone competitively inhibit CYP2D6 activity, whereas epiallopregnanolone and alfaxalone noncompetitively inhibit the same isoenzyme [24]. In addition, pharmacological studies revealed that estrogen-induced cholestasis can repress CYP2D6 expression and activity [25]. However, although the study protocol did permit the use of oral contraceptives during the clinical trial, an enquiry revealed that 50 % of the female subjects were using bar- AUC_ATX -area under the plasma concentration-time curve from time 0 to infinity for atomoxetine; AUC_HATX-gluc -area under the plasma concentration-time curve from time 0 to infinity for 4-hydroxyatomoxetine-O-glucuronide; MR_ AUC-metabolic ratio calculated as AUC_ATX / AUC_HATX-gluc rier contraceptive methods, while the rest did not report the use of any birth control method.…”
Section: Discussionmentioning
confidence: 99%
“…Significant association between CYP2D6 mRNA and activity levels was reported in human liver tissue . In addition, studies using CYP2D6 ‐humanized mice showed that transcriptional regulation of CYP2D6 can lead to serial changes in CYP2D6 protein and activity levels …”
mentioning
confidence: 99%
“…Genetic polymorphisms of CYP2D6 linked to no enzyme activity are known to contribute to the poor metabolizer, whereas increased copy number of normal function CYP2D6 alleles is associated with ultrarapid metabolizer phenotypes . Of interest, recent studies indicate that differential transcriptional regulation of CYP2D6 may in part explain the variability in CYP2D6‐mediated drug metabolism . Significant association between CYP2D6 mRNA and activity levels was reported in human liver tissue .…”
mentioning
confidence: 99%
See 1 more Smart Citation